Comparable Efficacy of Reduced Dose Radiation Therapy for the Treatment of Early Stage Gastric Extranodal Marginal Zone Lymphoma of Mucosa-Associated Lymphoid Tissue - Omran Saifi, MD; Scott C. Lester, MD; William Rule, MD; Bradley J. Stish, MD; Scott Stafford, MD; Deanna H. Pafundi, PhD; Liuyan Jiang, MD; David Menke, MD; Muhamad Alhaj Moustafa, MD; Allison Rosenthal, MD; Taimur Sher, MD; Ayala Ernesto, MD; et al. (Advances in Radiation Oncology, 2021)
Purpose: This study compares reduced (<27 Gy) to standard dose (≥30 Gy) radiation therapy (RT) in the treatment of gastric extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (gMALT lymphoma). Methods and Materials: Forty-two patients with stage I or II disease were retrospectively reviewed. Response to RT was assessed with endoscopy after RT. Complete response rate (CR), freedom from treatment failure, and overall survival (OS) were calculated. Results: All patients were stage I (n = 40) or II (n = 2). All patients had residual biopsy proven gMALT lymphoma before RT. Twenty-six patients (61.9%) were treated with standard dose RT, 30 to 36 Gy, and 16 (38.1%) with the reduced dose RT, 23.5 to 27 Gy. The median follow-up was 29.5 months (range, 6-85). Thirty-six patients (86%) achieved complete response (CR), and 6 patients (14%) achieved partial response (PR). The complete response rate (CR) at the first endoscopic assessment, median time of 3 months, was 81% (95% confidence interval, 0.61%-0.93%) for standard RT, and 94% (confidence interval, 0.69%-0.99%) for reduced RT. Among CR patients, one patient had locally relapsed disease at 50 months. The 1-year overall survival (OS) was 100% in both groups. The 1-year freedom from treatment failure (FFTF) was 100% in the reduced RT group and 92% in the standard RT group. The 2-year FFTF and OS of the whole cohort were 92% and 96%, respectively. There was no significant difference in the OS, FFTF, and CR between the 2 treatment groups (P = .38, P = .18, and P = .267, respectively). For toxicity, the mean liver dose and the mean V20 heart dose were significantly lower in the reduced RT group (P <.001 and P = .001, respectively). However, incidence and severity of reported toxicities were similar between the 2 groups. Conclusions: Reduced dose RT (23.5-27 Gy) achieved excellent complete response rates with minimal toxicity, comparable with standard dose RT (30-36 Gy), for gMALT.